In Situ Femtosecond-Laser-Induced Fluorophores on Surface of Polyvinyl Alcohol for H2O/Co2+ Sensing and Data Security - Weiliang Chen (MDPI AG, 2021)
In situ fluorophores were induced on polyvinyl alcohol (PVA) bulk materials by direct femtosecond laser writing. The generation of fluorophores was ascribed to localized laser-assisted carbonization. The carbonization of PVA polymers was confirmed through X-ray photoelectron spectroscopy analysis. The distinct fluorescence responses of fluorophores in various solutions were harnessed for implementing in situ reagent sensors, metal ion sensors, data encryption, and data security applications. The demonstrated water detection sensor in acetone exhibited a sensitivity of 3%. Meanwhile, a data encryption scheme and a “burn after reading” technique were demonstrated by taking advantage of the respective reversible and irreversible switching properties of the in situ laser-induced fluorophores. Taking a step further, a quantitative cobalt ion measurement was demonstrated based on the concentration-dependent fluorescence recovery. Combined with a laser-induced hydrophilic modification, our scheme could enable “lab-on-a-chip” microfluidics sensors with arbitrary shape, varied flow delay, designed reaction zones, and targeted functionalities in the future.